PENGARUH KEPRIBADIAN INTROVERT DAN EKSTROVERT TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT PUTRI AL-IHSAN WAHDAH KABUPATEN BANTAENG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of introverted and extroverted personalities on students’ academic achievement in Islamic Religious Education at SMP IT Putri Al-Ihsan Wahdah Islamiyah in Bantaeng Regency. This study employs a quantitative approach using an ex post facto method. The study population consists of 60 students, all of whom were selected as the sample using a saturated sampling technique. Data collection techniques included questionnaires and documentation, while data analysis utilized multiple linear regression with the assistance of SPSS software. The results of the study indicate that: (1) an introverted personality has a positive and significant effect on academic achievement, with a calculated t-value of 3.024 > the critical t-value of 1.296 and a significance level of 0.004 < 0.05, as well as a regression coefficient of 0.435; (2) extroverted personality has a positive and significant effect on academic achievement with a calculated t-value of 2.533 > the critical t-value of 1.296 and a significance level of 0.001 < 0.05, as well as a regression coefficient of 0.376; (3) Simultaneously, introverted and extroverted personalities have a significant effect on academic achievement, with a calculated F-value of 17.669 > the critical F-value of 3.16 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.383 indicates that 38% of academic achievement is influenced by introverted and extroverted personality traits, while the remaining 62% is influenced by other factors outside the scope of this study.